2007
DOI: 10.1039/b613157c
|View full text |Cite
|
Sign up to set email alerts
|

Switching the light emission of (4-biphenylyl)phenyldibenzofulvene by morphological modulation: crystallization-induced emission enhancement

Abstract: (4-Biphenylyl)phenyldibenzofulvene is weakly luminescent in the amorphous phase but becomes highly emissive upon crystallization; this unusual crystallization-induced emission enhancement effect allows its emission to be repeatedly switched between dark and bright states by fuming-heating and heating-cooling processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
143
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 402 publications
(148 citation statements)
references
References 30 publications
4
143
0
1
Order By: Relevance
“…TTAPE can thus be induced to emit light by restricting its intramolecular rotations, which is the exact cause for the AIE effect of its TBEPE cousin (see earlier). [15,20] DNA probing: G1 is a 21-mer ssDNA molecule that mimics the human telomeric sequence. When the DNA molecules are added into a solution of TTAPE in a tris(hydroxymeth-A C H T U N G T R E N N U N G yl)aminomethane (Tris)-HCl buffer solution, the solution starts to luminesce (Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…TTAPE can thus be induced to emit light by restricting its intramolecular rotations, which is the exact cause for the AIE effect of its TBEPE cousin (see earlier). [15,20] DNA probing: G1 is a 21-mer ssDNA molecule that mimics the human telomeric sequence. When the DNA molecules are added into a solution of TTAPE in a tris(hydroxymeth-A C H T U N G T R E N N U N G yl)aminomethane (Tris)-HCl buffer solution, the solution starts to luminesce (Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…[12] In this Communication, we report two trifluoromethyl (CF 3 )-substituted aromatic-amine compounds, diethyl-2,5-bis(4-(trifluoromethyl)phenylamino)terephthalate (AA-1) and diethyl-2,5-bis (3,5-bis(trifluoromethyl)phenylamino)terephthalate (AA-2), that display reversible thermally induced phase transformation accompanied by emission switching between different colors.…”
mentioning
confidence: 99%
“…Tang et al originally presented CIE-active organic compounds. 122 It was suggested that the regulation of intermolecular interactions in solid state is very important to develop CIE properties, boron diiminates with high functionality have a high potential as CIEactive materials. Figure 13 shows a representative example of a CIE-active compound 4 evaluated with X-ray diffraction (XRD) patterns and PL properties in the amorphous state and the crystalline state.…”
Section: ¹1mentioning
confidence: 99%